Standardization of the Childhood Autism Rating Scale (CARS2) on a Sample of Autistic Children in The Palestinian Interior (48) - Nassar, Raja'a Ebraheem Yasin (Journal of Educational and Psychological Sciences, 2025)
This study aimed to standardize the Childhood Autism Rating Scale–Second Edition (CARS2) prepared by Eric Schobler et al. (Al-Atwi, 2015), on a sample of children suspected of having autism spectrum disorder (ASD) in the Palestinian context, in order to examine its psychometric properties and provide a reliable diagnostic tool adapted to the local environment. The significance of the study stems from the increasing prevalence of ASD in Palestine, alongside the lack of culturally validated diagnostic instruments that support accurate early identification. The descriptive method was employed with a sample of children aged 3–8 years drawn from specialized centers. Findings indicated that the scale demonstrated acceptable levels of validity, with expert agreement rates ranging from 80% to 100%, and strong concurrent validity with the Gilliam Autism Rating Scale (correlation coefficient = 0.87). The CARS2 also showed good internal consistency (α = 0.74–0.83) and high test–retest reliability (0.92). Results further revealed variation in the distribution of ASD symptoms, with statistically significant differences by gender in favor of males, while no significant differences were found by age. The study concluded that the CARS2 is a valid and reliable diagnostic tool for identifying ASD within the Palestinian context. It emphasized the importance of early diagnosis in supporting therapeutic and educational interventions and recommended further validation on larger samples and examination of its relationship with additional variables.